2015
DOI: 10.7726/ajbb.2015.1004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single and Sequential Cellulolytic Enzyme Cocktail on the Fermentable Sugar Yield from Pretreated Agricultural Residues of Cassava

Abstract: Cassava cultivation generates three types of lignocellulosic residues such as stems, leaves and peels. As a part of the investigations on their potential for second generation (2G) bioethanol production, the effect of two cellulolytic enzyme cocktails in enhancing fermentable sugar yield from pretreated (hydrothermal and microwave assisted diluted acid treated) residues was studied. Highest release of reducing sugars was observed from cassava peels, followed by stems, during saccharification for 120 h with Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…38 and 73 g/L RS after 120 h saccharification, while ca. 27 g/L was only released from the leaves [26]. This showed that AHP treatment of steam-exposed slurry was superior to simple steam pretreatment in the case of leaves only.…”
Section: Fig2: Lignin Changes After Saccharification (120 H) Of Steamentioning
confidence: 75%
See 4 more Smart Citations
“…38 and 73 g/L RS after 120 h saccharification, while ca. 27 g/L was only released from the leaves [26]. This showed that AHP treatment of steam-exposed slurry was superior to simple steam pretreatment in the case of leaves only.…”
Section: Fig2: Lignin Changes After Saccharification (120 H) Of Steamentioning
confidence: 75%
“…Native (untreated) stem b. MW-assisted alkali pretreated stem c. Saccharified residue from MWassisted alkali pretreated stem d. Native (untreated) leaf e. MW-assisted alkali pretreated leaf f. Saccharified residue from MWassisted alkali pretreated leaf g. Native (untreated) peel h. MW-assisted alkali pretreated peel i. Saccharified residue from MWassisted alkali pretreated peel Fig. 4 (a-i) Pooja and Padmaja [26] reported the presence of alphaamylase existing as a co-activity along with cellulase and β-glucosidase in Cellic CTec 2. However, the levels may not be sufficient to bring about complete hydrolysis of starch.…”
Section: Ultrastructural Studiesmentioning
confidence: 99%
See 3 more Smart Citations